Clinical and sociodemographic analysis of people with ostomies: a cross-sectional study (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Objectives: To analyze clinical and sociodemographic aspects of people with ostomies in the state of Minas Gerais. Methods: A cross-sectional study was conducted in 54 municipalities in 2016. Data were collected from 418 people with ostomies, registered from a structured questionnaire. Descriptive data analysis, the Pearson chi-square test and the Bonferroni correction were performed. Results: The majority of people with ostomies are elderly, male, have low schooling and low wage income. Colorectal malignant neoplasia was the main cause and 14.3% were treated with chemotherapy. Part of the ostomies is of the regular standing permanent colostomy type. The main complication highlighted is dermatitis, and 45.5% are not able to develop self-care. The type of ostomy was significantly associated with stomatal permanence, marital status and income (p